PENGARUH KONDISI KEUANGAN, DEBT DEFAULT, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Wahyu Delta Setyanida; Ceacilia Srimindarti (SIMAK, 2021)
This research aims to examinethe effect of. financial. condition, debt. default, size, and.Growth on going. concern. audit. opinion. All. manufacturing. companies. listed.onthe. Indonesia. Stock. Exchange. from. 2017. to. 2019 are. used. in. this. study. as.a population. Sample method used in this research is purposive sampling. The. samples. obtained. in. this. study. were. 215 samples. from. 494 manufacturing. companies. The method of analysis used in this research is logistic. regression.Analysis.The result of this research found that. financial. condition, debt. default, size, and growth. does. not. have. a significant.Impacton. going. concern. audit. opinion.The results of this study have implications for the company in order to avoid going concern audit opinion.